Association between Alopecia Areata and Thyroid Dysfunction in Western Nepal - Shrestha, Pratistha; Shrestha, Meera; Gurung, Sabhayata (Nepal Journal of Medical Sciences, 2023)
Introduction: Alopecia areata is an autoimmune disease characterized by patchy loss of hair. The etiopathogenesis of the disease is still unclear, but the role of autoimmunity is strongly suggested. Alopecia areata is associated with autoimmune thyroiditis and diabetes mellitus. So the main aim of this study is to study the association between alopecia areata and thyroid dysfunction. Methods: We conducted a cross-sectional observational study involving 105 patients with alopecia areata. Thyroid function tests (free T3, T4, TSH ) were performed in all the patients with alopecia areata. Data were analyzed using SPSS, version 20. A p-value of less than 0.05 was considered statically significant. Results: Within alopecia areata patients, in only one male patient (1.9%) T3 was abnormal, in four female patients (7.5%) and six male patients (11.5 %) T4 was abnormal, and in six female patients (11.3%) and three male patients (5.8%) TSH was abnormal. Conclusion: In our study, there was no significant association between alopecia areata and thyroid function tests.